Physical activity programmes in the elderly: a successful strategy for healthy ageing - Shenda Orrego Molina; Luis García-Gonzalez; Berta Murillo Pardo; Javier Zaragoza Casterad; Alberto Aibar Solana (Asociación Española de Ciencias del Deporte, 2018)
Background: Because the elderly are the most inactive and sedentary segment of the population, public institutions have created new programmes of regular and organised physical activity (PA). However, whether these programmes suffice to comply with the WHO recommendations on physical activity is unknown. In this study, we aim: a) to describe the levels of PA and sedentary behaviour in a group of elderly members of a PA programme organised by the City of Huesca (Spain); b) to evaluate their compliance with the recommended daily practice of PA; and c) to determine the sedentary activities that they spend the most time on, identifying factors that may influence both PA levels and sedentary behaviours. Methodology: A descriptive, cross-sectional study was performed, consisting in a questionnaire of sedentary behaviours. PA was measured by accelerometery. Results: International recommendations for PA are met by 84.4% of the subjects, evidencing higher levels of PA on the days when they attend fitness classes. The most common sedentary activity was watching television. Conclusions: The elderly participating in PA programmes organised by public institutions seem to benefit from higher levels of moderate to vigorous PA, evidenced by a high percentage of compliance with the international PA practice recommendations. We recommend continuing to foster the availability of PA programmes organised by municipal institutions.